Nitrogen Response to Pearl Millet (Pennisetum Typhoides S + H) Grown on Soil Underneath P. Cineraria and Adjacent Open Site in an Arid Environment - Aggarwal, R K; Kumar, Praveen (Annals of Arid Zone, 2016)
The response of fertilizer N to pearl millet grown on two soils i.e. soil under Prosopis cineraria tree( Khejrt soil, and adjacent open site soil (non-khejri soil was studied under greenhouse condition. An increase in dry matter yield to the extent of 73 per cent on khejri soil over non khejri soil indicated an enhanced fertility build up in soil underneath P. cineraria. The N-use efficiency increased from 27% (non-khejri soil) to 46% in khejri soil at 140 mg N kg-1 soil application. The response to N on dry matter yield was observed upto 280 mg N kg-1 soil. The uptake of N,S, and P and percent N in plant was higher on khejri soil as compared to non-khejri soil at all the N-levels.